Disiplin Kerja dan Efektivitas Organisasi pada Lembaga Tanggap Darurat: Studi Kasus BASARNAS di Kendari - Bakhtiar Abbas; Rince Tambunan; Sitti Hajrah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study investigates and analyzes work discipline and organizational effectiveness at the Kendari Office of the National Search and Rescue Agency of Indonesia (BASARNAS). Work discipline and effectiveness are critical factors in ensuring optimal employee performance, particularly in emergency response operations. Data were collected through interviews and documentation, employing a qualitative descriptive methodology. A descriptive approach in data analysis was used to clarify employees' levels of discipline and job efficiency. The findings reveal that work discipline at the BASARNAS Kendari Office has been well implemented, adhering to established work standards and regulations. Employees demonstrate a high level of commitment and compliance, contributing to maintaining operational efficiency. Furthermore, employee effectiveness is considered relatively high, as personnel are able to perform their duties efficiently and in alignment with organizational objectives. Based on these results, work discipline and effectiveness at the BASARNAS Kendari Office are generally well maintained, supporting smooth operations and high levels of performance. To further enhance outcomes, it is recommended that continuous training and performance evaluations be conducted to strengthen discipline and improve efficiency in emergency response operations. These findings suggest that maintaining strict discipline and closely monitoring work effectiveness are essential for optimizing organizational performance in high-risk environments.